Clinical performance of different DF‐4 implantable cardioverter defibrillator leads. Issue 8 (29th June 2018) - Sarrazin, Jean‐François; Philippon, François; Sellier, Romain; André, Philippe; O'Hara, Gilles; Molin, Franck; Nault, Isabelle; Blier, Louis; Champagne, Jean
Abstract: Introduction: Implantable cardioverter‐defibrillator (ICD) DF‐4 connectors have been introduced to facilitate defibrillator lead connection and to reduce the size of device header. There are limited data regarding the overall performance of those leads and no comparison between different ICD DF‐4 leads. Methods: This is a cohort study of consecutive patients implanted with ICD DF‐4 lead system at one University Centre between October 2010 and February 2015. A historical control group of patients with ICD DF‐1 lead implantation was used for comparison. The following ICD DF‐4 leads were evaluated: St. Jude Medical Durata 7122Q (St. Jude Medical, St. Paul, MN, USA), Medtronic Sprint Quattro Secure 6935 M (Medtronic Inc., Minneapolis, MN, USA), Boston Scientific Endotak Reliance 4‐Site 0293 (Boston Scientific, Marlborough, MA, USA), and Boston Scientific Reliance 4‐Front 0693. This study evaluated the acute and mid‐term performances of those leads as well as complications. Results: A total of 812 patients (age 63 ± 12 years, 80% male, left ventricular ejection fraction 31 ± 12%) underwent implantation of an ICD DF‐4 lead. Acute and follow‐up R‐wave sensing and threshold were excellent. Compared to implantation, intrinsic R waves were higher at follow‐up for Boston Scientific and Medtronic leads, and pacing lead impedances were lower for all leads at first follow‐up (P < 0.001). The number of lead dislodgement or failure was similar between all leads. The estimated lead survival rates at 3 years were 95.6% for Boston Scientific Endotak 4‐Site, 97.1% for Boston Scientific 4‐Front, 97.7% for Medtronic Sprint Quattro, and 97.5% for St. Jude Durata (P  =  0.553). Conclusion: All ICD DF‐4 leads had excellent acute and mid‐term electrical performances. Longer follow‐up will be necessary to confirm their sustained performance.